A vajdasági magyarlakta térség felzárkózásának az esélye - Gábrity Molnár, Irén (Közép-Európai Közlemények, 2011)
Human capital in every country, therefore in Serbia as well plays a crucial social and economic role. As a result of political problems, the long change of economic structure, the unsuccessful privatization the human capital has been damage. The majority of the inhabitants suffered an economic, intellectual and moral loss of importance. The experts have stated several time: •The structural transformation of the economy (transition, EU accession prospects) is not followed by the changes of education and employment policy. There is no communication, institutionalized cooperation between the institutions that plays a crucial role in the development of the region’s human capital. •Individuals (employees, unemployed) make ad hoc decisions in their effort to accommodate to the human labor market expectations. Long term unemployment will raise migration intentions. •The republic power institutions are not willing to give up their central institutional legitimacy. Decentralized is denied even when economic rationality would require such decision. Therefore, the development of infrastructure and the economic developmental strategies of the local institutions are not harmonized.